2019
DOI: 10.26873/svr-791-2019
|View full text |Cite
|
Sign up to set email alerts
|

DIAGNOSIS AND PHYLOGENETIC ANALYSIS OF THE CIRCULATING PESTE DES PETITS RUMINANTS VIRUS IN Al-SHARQIA GOVERNATE

Abstract: Peste des petits ruminants (PPR) is a Morbillivirus within the Paramyxoviridae family which characterized by highly contagious nature with high morbidity and mortality rates in domestic small ruminants. The aim of this study was to investigate an outbreak of P PRV in a flock of sheep and goats in Belbes city, AL-Sharqia governorate in 2018 by virus isolation and conventional RT-PCR. Phylogenetic analysis of N gene sequence of PPRV isolate. Also, compare it with other isolate from previous outbreak in Zagazig c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Another study by Nafea et al [37] revealed that antibodies were detected in five sheep sera samples (5/7; 71.4%) using C-ELISA, and they stated that PPRV is still circulating in Egypt, leading to outbreaks in its major host (small ruminants); therefore, an effective PPR vaccination program is recommended to be regularly administered in Egypt along with strict Available at www.veterinaryworld.org/Vol.13/August-2020/25.pdf quarantine measures at the borders to prevent the introduction of new PPRV genotypes [38]. Sudanese strain caused a PPR outbreak in Ismailia, Egypt in 2010 and 2012 [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Nafea et al [37] revealed that antibodies were detected in five sheep sera samples (5/7; 71.4%) using C-ELISA, and they stated that PPRV is still circulating in Egypt, leading to outbreaks in its major host (small ruminants); therefore, an effective PPR vaccination program is recommended to be regularly administered in Egypt along with strict Available at www.veterinaryworld.org/Vol.13/August-2020/25.pdf quarantine measures at the borders to prevent the introduction of new PPRV genotypes [38]. Sudanese strain caused a PPR outbreak in Ismailia, Egypt in 2010 and 2012 [23].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, an outbreak in 2006 in the Aswan Province once again highlighted the potential for infected goats to occasionally be asymptomatic, while others develop a severe medical disorder [ 22 ]. A study [ 23 ] also performed a genetic analysis of PPRV and found that on comparing the N gene sequence of both PPRV isolates, they saw that there is a homogenous population of PPR virus isolates of up to 99%. The PPRV isolates used in their study and all preceding Egyptian isolates belong to lineage IV in terms of phylogenetic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, lineage IV has been found in a larger number of countries. Since its first detection in Israel in 1993 [ 35 ], its presence has been evidenced in Egypt 2012 [ 36 , 37 , 38 ], Iran [ 39 , 40 ], Iraq [ 41 ], Jordan [ 42 ], Kuwait [ 33 ], Palestine [ 43 ], the KSA [ 30 , 44 ] and the UAE [ 45 ]. No PPR sequences are available for Bahrain and Lebanon.…”
Section: Ppr Situation At the Regional Levelmentioning
confidence: 99%
“…In 2012, PPR outbreaks were documented in sheep flocks in the Ismailia and Cairo Governorates [ 17 , 36 ], leading to the development and application of a national strategy to control the disease. Subsequently, PPR has been reported annually ( Figure 5 ) and multiple studies have found considerable seroprevalence rates in unvaccinated SRs sampled in different governorates [ 37 , 38 , 54 , 55 , 56 ].…”
Section: Ppr Situation At the National Levelmentioning
confidence: 99%
“…As PPR disease consider a hurdle to sustainable agriculture development through Africa, using recent confirmatory molecular tools in PPRdiagnosis were proved to be sensitive and specific to detect the genome of PPR virus [10] and opened a new way of disease investigation to be recommended by OIE.Mainly, two standard PCRs, Reverse transcription (RT-PCR) and quantitative real-time RT-PCR have been developed to amplify parts of the fusion (surface glycoprotein), or the nucleoprotein (most abundant internal protein), or the matrix protein genes [11], thus helps in genetically typing the PPRV isolates from different outbreaks and then subsequent assessment of the epidemiological lineage distribution in endemic areas of Africa, thus leading to speculating the dominant lineage emergence of PPRV in new areas [11].Genetically, the Egyptian isolates have been identified as belonging to lineage IV,and this lineage is becoming the predominant lineage in Africa, suggesting that perhaps Egypt is the gateway for the predominantly PPRV Asian lineageentry into Africa [12,13].…”
Section: Introductionmentioning
confidence: 99%